2022
DOI: 10.1007/s10639-022-10899-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated HE digitalisation: Exploring staff and student experiences of the COVID-19 rapid online-learning transfer

Abstract: In the UK, the first ‘lockdown’ of the COVID-19 pandemic necessitated a rapid shift to online learning and digital technologies in Higher Education (HE). While the situation was unprecedented, extant literature on online learning suggested there would be challenges, opportunities, and benefits to this transition, and we sought to understand these via a case study of one UK HEI department at this time. To draw out in-depth and nuanced accounts of this (at time of investigation–unstudied) scenario, qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 54 publications
0
28
0
1
Order By: Relevance
“…Around one-tenth of the respondents indicated a lack of reliable access to a PC (e.g., had to share a PC with other members of their family) and/or a computer without a camera and/or microphone, while a small number reported a lack of reliable access to any technology during the first lockdown. Although no information concerning students' socio-economic background was collected in the current study, limited access to hardware devices has been identified in the international literature as a barrier to effective remote studying in low-and middle-income households during the pandemic [44], and so has been the lack of a dedicated study space [18,44,45,47,49,50], which was also an issue for several of the students in our study. Specifically, around eight percent of the respondents (n = 86) stated that they did not have a dedicated study area at all and that they had to move from place to place around the house to be able to study.…”
Section: Challenges In the Transition To Erlmentioning
confidence: 95%
See 4 more Smart Citations
“…Around one-tenth of the respondents indicated a lack of reliable access to a PC (e.g., had to share a PC with other members of their family) and/or a computer without a camera and/or microphone, while a small number reported a lack of reliable access to any technology during the first lockdown. Although no information concerning students' socio-economic background was collected in the current study, limited access to hardware devices has been identified in the international literature as a barrier to effective remote studying in low-and middle-income households during the pandemic [44], and so has been the lack of a dedicated study space [18,44,45,47,49,50], which was also an issue for several of the students in our study. Specifically, around eight percent of the respondents (n = 86) stated that they did not have a dedicated study area at all and that they had to move from place to place around the house to be able to study.…”
Section: Challenges In the Transition To Erlmentioning
confidence: 95%
“…Thirty-one (n = 31; 3%) of the participants stated that they faced accessibility issues in their courses due to disabilities and/or other educational needs. Other studies [44,45,73] also found that students with special needs or disabilities were not adequately supported for effective e-learning. Even in educational contexts where inclusion is imperative and digital inclusion is embraced, the needs of students with additional support needs were difficult to meet remotely [73][74][75].…”
Section: Challenges In the Transition To Erlmentioning
confidence: 99%
See 3 more Smart Citations